Laser-assisted 3D printing of carbon fibre reinforced plastic parts. (January 2022) - Nakagawa, Yuki; Mori, Ken-ichiro; Yoshino, Masahiko
Abstract: Laser-assisted 3D printing process of fabricating carbon fibre reinforced plastic parts by sandwiching fibres between plastic layers was developed to improve the bond strength of the fibres to the plastic layers. Here, bundled carbon fibres are placed on the 3D-printed lower plastic layer, and the upper plastic layer is deposited on the fibres. Next, the two layers sandwiching the fibres are laser-heated using a blue diode laser beam. The plastic colour changed the heating temperature at the interface between the fibres and the plastic layer due to the transmittance and absorption phenomena; the translucent layer having high transmittance was most appropriate. The strength and rigidity of the 3D-printed carbon fibre reinforced plastic parts were improved by laser heating. Carbon fibre reinforced plastic parts having closed cross-sections are manufactured and strengthened by optimising the sandwiched fibre orientation. Besides, a tailored part locally reinforced by the carbon fibres is easily 3D-printed, and the deformation behaviours are observed.